Before Valentinus: The Gnostics of Irenaeus - Thomassen, Einar, (Nag Hammadi and Manichaean Studies ;, 2023)
This book offers the first detailed commentary on the Gnostic treatises reported by Irenaeus in Adversus Haereses 1.29-30. It is argued that these texts represent the earliest tangible layer of the Gnostic literary tradition and served as sources for the Apocryphon of John and other later works. They also formed the starting point for Valentinus and his followers, who sought to reconcile the ideas of the Gnostics with apostolic Christianity. The book also shows that Irenaeus and later heresiologists referred to "the Gnostics" as a specific group among the great mass of heretics.